Prototype Development Model Application Visualization Jarimatika Simple and Interest Based Website for Early Childhood Education - Maria Atik Sunarti Ekowati; Darsini Darsini (Proceeding Of The International Seminar and Conference on Global Issues, 2016)
A process that produces prototype called prototyping. Prototype development steps: identify, develop, define Prototype accepted, use, coding, testing, determine the system that has received the user, use. The study was conducted  on  children  in  kindergarten  and  early  childhood  Dikspora  Surakarta  Regional  Office,  2014   and  2015, financed  Higher  Education,  and  has  produced  a  model  of  visualization  applications  Jarimatika  simple  as  a refinement  of  research  conducted  in  2012  in  SD  Canisius  Semanggi,  Surakarta.  The  purpose  of  research  is  to develop a model visualization Jarimatika with WEB-based model design. The process of learning mathematics in schools  was  introduced  through  a  WEB-based  Jarimatika  method.  And  through  the  website  are  expected  to Prototype Development Model Application Visualization Jarimatika Simple and Interest Based WebSite For Early Childhood Education, translate into something useful for the development of the nation, as the future generation. From the research results can be seen that the technique Jarimatika is very important for the study of mathematics, especially  early  childhood,  therefore,  the  development  of  prototype  model  of  application  visalisasiJarimatika  is  a solution that can help children to learn mathematics, and bring in the website is part of the technology development appropriate, so that parents can specifically learn through your online  media on the internet, and not just parents student of 20 samples in the region of Surakarta official who can learn but all those who want browshing and willing to  learn  Jarimatika  through  internet  media  online.  Basic  application  development  using  Macromedia  Flash Professional 8 Portable Version, a programming language Action Script and XML database, the design view wear Makromedia flash Prof 8 and adophe firework, phpMyAdmin database design and Sequel Pro and output Prototype Model Visualization Jarimatika.Keywords: Prototype, Model, Visualization, Jarimatika, Website